Factors Influencing Management Student Competency Development: The Impact of Learning Quality, Satisfaction, and Learning Environment on Academic Achievement Through Motivation and Self-Efficacy - Kusjono, Gatot; Widodo, Sugeng; Suprianto, Suprianto (Universitas Pamulang, 2025)
Background: The development of management student competencies has become increasingly crucial in contemporary higher education, particularly as institutions strive to enhance academic outcomes and prepare students for dynamic professional environments. This study examines the complex relationships between learning quality, satisfaction, learning environment, and academic achievement, with motivation and self-efficacy serving as mediating variables. Methods: This quantitative study employed a structural equation modeling approach using Smart PLS 4.0 to analyze data from management students. The research utilized a cross-sectional survey design with validated instruments measuring learning quality (X1), satisfaction (X2), learning environment (X3), motivation (Y1), self-efficacy (Y2), and academic achievement (Z). The study applied bootstrapping procedures to test path coefficients and indirect effects, with all constructs demonstrating adequate reliability and validity. Results: The analysis revealed that learning environment (X3) had the strongest direct effect on both motivation (β = 0.636, p < 0.001) and self-efficacy (β = 0.526, p < 0.001). Learning quality significantly influenced both motivation (β = 0.183, p = 0.020) and self-efficacy (β = 0.291, p < 0.001). Satisfaction showed significant effects on self-efficacy (β = 0.150, p = 0.005) but not on motivation (β = 0.117, p = 0.066). Self-efficacy demonstrated a stronger mediating effect on academic achievement (β = 0.589, p < 0.001) compared to motivation (β = 0.341, p < 0.001). The model explained 78.4% of variance in motivation, 81.5% in self-efficacy, and 81.4% in academic achievement. Conclusions: The findings highlight the critical role of learning environment in fostering student competency development, with self-efficacy serving as a more powerful mediator than motivation in translating learning experiences into academic achievement. These results provide valuable insights for educational practitioners and policymakers in designing effective management education programs.